Gender influence on selection and outcome of deep brain stimulation for Parkinson′s disease - Shyambabu Chandran; Syam Krishnan; Ravi Mohan Rao; S Gangadhara Sarma; P Sankara Sarma; Asha Kishore (Annals of Indian Academy of Neurology, 2014)
Background: Gender differences exist in Parkinson′s disease (PD), both in clinical manifestations and response to medical treatment. We investigated whether gender differences occur in the clinical characteristics of patients selected for bilateral subthalamic nucleus deep brain stimulation (STN DBS) or in the outcome when resource limits influence treatment choices made by patients. Materials and Methods: Fifty-one consecutive patients were evaluated 1 month before, and 12 months after bilateral STN DBS. All patients were rated using Unified Parkinson′s Disease Rating Scale, Parkinson′s Disease Quality of Life (PDQL) Scale, Addenbrooke′s Cognitive Examination and Beck Depression Inventory. Results: Pre-operative characteristics did not differ between the genders except for lower doses of drugs (P = 0.03), worse emotional scores in PDQL (P = 0.01) and worse depression (P = 0.03) in women. There was no gender difference in the surgical outcome, except a lesser reduction of dopaminergic drugs in women. Depression and quality of life (QOL) improved equally well in women and men. Conclusion: Bilateral STN DBS is equally efficacious in both genders as a treatment for motor complications of PD and for improving QOL. Women are likely to be undertreated because of more severe dyskinesia and may experience less emotional well-being, and could therefore potentially benefit from earlier surgical treatment.